Improved Cu2O‐Based Solar Cells Using Atomic Layer Deposition to Control the Cu Oxidation State at the p‐n Junction. Issue 11 (4th April 2014) - Lee, Sang Woon; Lee, Yun Seog; Heo, Jaeyeong; Siah, Sin Cheng; Chua, Danny; Brandt, Riley E.; Kim, Sang Bok; Mailoa, Jonathan P.; Buonassisi, Tonio; Gordon, Roy G.
<x xml:space="preserve">Abstract</x> Solar cells are produced by atomic layer deposition (ALD) of n‐type amorphous zinc‐tin‐oxide buffer layers on electrochemically deposited p‐type cuprous oxide, Cu2O, absorber layers. The diethylzinc precursor in the ALD process reduces Cu2+‐related defects at the heterojunction interface, improving the solar‐cell open‐circuit voltage. An NREL‐certified power conversion efficiency of 2.85% is reported. <boxed-text content-type="graphic" position="anchor" orientation="portrait"> </boxed-text>